2007
DOI: 10.4103/0255-0857.32715
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile of community acquired acute bacterial meningitis: A ten-year retrospective study in a tertiary neurocare centre in South India

Abstract: Streptococcus pneumoniae remains the major aetiological agent of CAABM both in adults and children in our set-up. No penicillin resistance was detected among the isolates. Further research should focus on preventable aspects of CAABM, especially pneumococcal vaccines, to help reduce the disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 12 publications
5
34
0
1
Order By: Relevance
“…Two hospital-based retrospective studies from India were included in this review [20], [27]. The pooled data showed that S. pneumoniae was present in 28.36% (95% CI 22.74–79.46) of isolates from the total number of admitted patients with invasive bacterial diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Two hospital-based retrospective studies from India were included in this review [20], [27]. The pooled data showed that S. pneumoniae was present in 28.36% (95% CI 22.74–79.46) of isolates from the total number of admitted patients with invasive bacterial diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Öncesinde antibiyotik kullanımı ile bu oran %20'lere kadar düşmektedir (9) . Çeşitli çalışmalara %4.1 (20) , %40.4 (21) , %65.7 (22) gibi çok farklı oranlarda tanıya katkısı bildirilmiştir. Çalışmamızda, 19 hastanın 5 (%26.3)'inde Gram boyama ile mikroorganizma belirlenmiştir.…”
Section: Discussionunclassified
“…It has been reported that neonatal meningitis can occur in the absence of bacteraemia and no single cerebrospinal fluid (CSF) value can exclude its presence3. Several studies from India have reported the spectrum of bacterial pathogens and the existence of antibiotic resistance among the isolates from neonatal sepsis/meningitis cases4567. We have earlier isolated rarely encountered bacteria including Neisseria meningitidis serogroup Y8, Sneathia 9 and Globicatella (unpublished) species from CSF of neonates from north-east India.…”
mentioning
confidence: 94%